2021
DOI: 10.1155/2021/8686550
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Group B Streptococcus Colonization in Pregnant Women: A Pilot Study in Palestine

Abstract: Background. Maternal Streptococcus agalactiae (Group B Streptococcus (GBS)) colonization is an important cause of complications in mothers and neonates during gestation and after delivery. The data regarding GBS colonization among pregnant women in Palestine is scarce. The aim of this study is to determine the prevalence of GBS colonization, its associated risk factors, and the antibiotic sensitivity patterns in Nablus, West Bank, Palestine. Methods. A cross-sectional, single center study conducted at Rafidia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
3
1
Order By: Relevance
“… 51 The percentage of susceptibility to clindamycin was 83.3%, which was consistent with studies reported from Ethiopia (86.4%) 46 and Asia (84%). 57 However, it is higher than the study reported from Bahir Dar city (66.7%), 31 Palestine (70.8%), 52 and Italy (56.25%). 50 Since clindamycin is another alternative antibiotic recommended by the CDC for pregnant women who are allergic to penicillin, the resistance level underlines the need to carry out a susceptibility test.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“… 51 The percentage of susceptibility to clindamycin was 83.3%, which was consistent with studies reported from Ethiopia (86.4%) 46 and Asia (84%). 57 However, it is higher than the study reported from Bahir Dar city (66.7%), 31 Palestine (70.8%), 52 and Italy (56.25%). 50 Since clindamycin is another alternative antibiotic recommended by the CDC for pregnant women who are allergic to penicillin, the resistance level underlines the need to carry out a susceptibility test.…”
Section: Discussioncontrasting
confidence: 56%
“…The percentage of nonsusceptibility to erythromycin (27.8%) was correlated with studies conducted in Gondar (26.5%), 20 South America (31.6%), 49 Palestine (25%) 52 and Korea (28%). 57 The current CDC advice that an antibiotic susceptibility test should be carried out if erythromycin medication is required to prevent neonatal GBS infection is highly supported by the rate of erythromycin resistance in the GBS isolates.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations